The HMG-I/Y-related protein p8 binds to p300 and Pax2 trans-activation domain-interacting protein to regulate the trans-activation activity of the Pax2A and Pax2B transcription factors on the glucagon gene promoter - Hoffmeister, A. (2002)
p8 is a nuclear DNA-binding protein, which was identified because its expression is strongly activated in response to several stresses. Biochemical and biophysical studies revealed that despite a weak sequence homology p8 is an HMG-I/Y-like protein, suggesting that p8 may be involved in transcription regulation. Results reported here strongly support this hypothesis. Using a pull-down approach, we found that p8 interacts with the general co-activator p300. We also found that, similar to the HMG proteins, p300 was able to acetylate recombinant p8 in vitro, although the significance of such modification remains to be determined. Then a screening by the two-hybrid system, using p8 as bait, allowed us to identify the Pax2 trans-activation domain-interacting protein (PTIP) as another partner of p8. Transient transfection studies revealed that PTIP is a strong inhibitor of the trans-activation activities of Pax2A and Pax2B on the glucagon gene promoter, which was chosen as a model because it is a target of the Pax2A and Pax2B transcription factors. This effect is completely abolished by co-transfection of p8 in glucagon-producing InRIG9 cells, indicating that p8 binding to PTIP prevents inhibition of the glucagon gene promoter. This was not observed in NIH3T3 fibroblasts that do not express glucagon. Finally, expression of p8 enhances the effect of p300 on Pax2A and Pax2B trans-activation of the glucagon gene promoter. These observations suggest that in glucagon-producing cells p8 is a positive cofactor of the activation of the glucagon gene promoter by Pax2A and Pax2B, both by recruiting the p300 cofactor to increase the Pax2A and Pax2B activities and by binding the Pax2-interacting protein PTIP to suppress its inhibition.